Case studies in educational administration - Laforteza, Carmencita Ponce 1930- (1977)
This study aimed to develop cases in educational administration for instructional purposes, to develop a kind of methodology in writing cases out of the personal experiences, reading of voluminous legal documents and converting/rewriting them into nonlegal form, and to provide future case writers with criteria and steps in locating cases, including and excluding data, and writing cases. The researcher principally made use of documentary approach of gathering data supplemented by personal interviews with people involved or had knowledge on case writing. Teaching objectives/guidelines for each case were likewise drawn out to guide future case users.
Appendices: [17] leaves
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: School management and organization -- case studies. -- Philippines